Análisis de producción gonadal del pez Grundulus quitoensis Román-Valencia, Ruiz-C. y Barriga, 2005 (Characiformes: Characidae) en la laguna altoandina “El Voladero” provincia El Carchi, Ecuador (2016)
Relative fecundity in fishes is the estimated number of oocytes of a female during spawning. This aspect was investigated in Grundulus quitoensis topotypic specimens from the “El Voladero”, a high Andean lake in Ecuador. Gonad maturation stages (mature and immature) were identified by means of direct observation, subsequently, the relative fertility (FRP) as function of the weight and the total length (TL) were calculated. Average TL of females was 63.9 mm. The numbers of oocytes ranged from 75 to 716 per female, in total 5691 oocytes were counted from 16 females. TW ranged from 0.5 to 4.7 g, whereas TL ranged from 36.7 to 63.9 mm. Relative fecundity ranged from 1.6 to 14.3 oocytes per mm TL (= 6.9 ± 3.6 mm-1) and from 47.2 to 319.1 oocytes per g of TW (= 148.9 ± 74.9 g-1). It is important to know the life cycle and natural history of a species, since they contribute to the ecological knowledge of the fishes that inhabit the high Andean lakes, as is the case of this study of G. quitoensis.